Keefektifan Media Pembelajaran Video Materi Matematika Pecahan Secara Daring di Sekolah Dasar - Ayuk Sri Windarti; M. Yusuf Setia Wardana; Bagus Ardi Saputro (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
Learning media has an important role in attracting students' interest and as an intermediary for learning activities from teachers to students. The difficulties that exist in mathematics subject require the creativity of mathematics subject teachers to develop their learning, both in terms of methods and media used. This study aims to determine the effectiveness of video learning media for fractional mathematics online in elementary schools. There is an experimental class and a control class from class V from elementary school. The results showed that the use of video learning media for fractional mathematics was effective. The errors that still appear after the research is done are that there are still some students who have not equated the denominator when working on the problem.